2022
DOI: 10.3389/fpubh.2022.992222
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up community-delivered mental health support and care: A landscape analysis

Abstract: IntroductionThe mental health crisis has caused widespread suffering and has been further exacerbated by the COVID-19 pandemic. Marginalized groups are especially affected, with many concerns rooted in social determinants of mental health. To stem this tide of suffering, consideration of approaches outside the traditional biomedical model will be necessary. Drawing from task-sharing models of mental health care that have been pioneered in low-resource settings, community-initiated care (CIC) represents a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The communities in the zip codes included have experienced the cumulative impact of multiple environmental disasters in the last decade [ 47 ]. Through a community-based process, the HMHC team identified the need for a broader focus on resiliency across multiple catastrophic events rather than a narrower focus on suicide, as initially intended [ 35 , 45 , 47 ]. In a microcosting study of intervention development, Lairson and colleagues found personnel contributing 69% of the cost [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The communities in the zip codes included have experienced the cumulative impact of multiple environmental disasters in the last decade [ 47 ]. Through a community-based process, the HMHC team identified the need for a broader focus on resiliency across multiple catastrophic events rather than a narrower focus on suicide, as initially intended [ 35 , 45 , 47 ]. In a microcosting study of intervention development, Lairson and colleagues found personnel contributing 69% of the cost [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broader social and environmental context of the athlete’s personal factors such as age, gender, socioeconomic status and the athlete’s impairment played a role in mental health 4–6 50. Furthermore, many HCPs acknowledged it was likely that athletes in their country sought care from religious, spiritual or cultural healers and experienced language barriers during healthcare 51 52. These contextual influences need to be investigated further within developing countries, where healthcare is not as aligned to the western biomedical system 32 33 40 43.…”
Section: Discussionmentioning
confidence: 99%
“…Its approach is community-based and allows for collaboration between health professionals and non-specialists increasing the availability of staff. However, its effectiveness depends on funding, ongoing training and the active participation of community leaders and other stakeholders [ 50 ].…”
Section: Discussionmentioning
confidence: 99%